The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1530/jrf.0.0610347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of castration on specific glycoprotein secretions of the epididymis in the rabbit and hamster

Abstract: Summary. Mature male rabbits and hamsters were bilaterally castrated and their epididymides were examined, at 2, 4, 7, 9 and 14 days after operation, for the presence of several glycoproteins by using monospecific antisera and indirect immunoperoxidase labelling. In the rabbit, there was a reduction in the glycoprotein reaction product in the epithelium of the proximal caput epididymidis by 2\p=n-\4days after castration, and the staining was weak or absent by 7\p=n-\9 days. Compared with controls, there was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The best known are androgens, i.e., testosterone and its metabolite, dihydrotestosterone. Androgens regulate specific gene expression in the epididymal epithelium [7][8][9], and androgen withdrawal produces dramatic changes in the pattern of secreted proteins in every region [9]. Most of these changes are reversed by androgen administration [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The best known are androgens, i.e., testosterone and its metabolite, dihydrotestosterone. Androgens regulate specific gene expression in the epididymal epithelium [7][8][9], and androgen withdrawal produces dramatic changes in the pattern of secreted proteins in every region [9]. Most of these changes are reversed by androgen administration [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Castration has been shown to have adverse effects on nearly all epididymal functions and many of these depend on the presence of androgens (Orgebin-Crist et al, 1975;Robaire and Hermo, 1988). The synthesis and secretion of a large number of glycoproteins and the activity of a number of enzymes are to a large extent regulated by androgens (Bohmer et al, 1977;Jones et al, 1980;Brooks, 1981Brooks, ,1983Moore, 1981;Robaire and Hales, 1982). Testosterone replacement has been shown to prevent the negative effects on protein secretion and enzyme activity after castration or hypophy- sectomy (Dyson and Orgebin-Crist, 1973).…”
Section: Effects Of Castrationmentioning
confidence: 99%
“…This may reflect either a suppression of glycoprotein secretion or an increase in glycoprotein breakdown. Using monospecific antisera and immunoperoxidase labeling, however, Moore (1981) reported that specific glycoproteins are not secreted into the lumen of the rabbit epididymis after castration and that their synthesis is reduced. The glycoproteins can be visualized at the lu- menal border even when the immunostaining has disappeared from the epithelium and the lumen.…”
Section: Castrated Rabbitsmentioning
confidence: 99%